Biodegradable ureteral stents for the treatment of urothelial tumors of the upper urinary tract cancer - Barros, Alexandre António Antunes (2016)
Publicado em "European cells and materials". ISSN 1473-2262. Vol. 31, suppl. 1 (2016)